Beyond the law: Exploring the impact of criminalising anabolic–androgenic steroid use on help-seeking and health outcomes in Australia - Piatkowski, Timothy (Journal of criminology, 2024)
This study aimed to investigate how Anabolic–Androgenic Steroid (AAS) users and healthcare professionals perceive the criminalisation of AAS on users’ ability to seek help and, ultimately, what effect this has on the health outcomes for these consumers. This study triangulated the views (N = 24) of male (n = 8) and female (n = 7) AAS users (Mage = 35.4, SD = 9.1), as well as healthcare providers (n = 9), regarding how the criminalisation of AAS had an impact on consumers’ health behaviours and help-seeking. Data were analysed thematically. An overarching narrative was developed regarding the “politicogenic drug effects” which emerge from the illegality of AAS with three overarching themes. First, participants expressed challenges in seeking help and support due to the stigma and fear associated with the illegal nature of AAS use. This fear stemmed from the criminalisation of AAS and the potential legal consequences. Participants also highlighted the social challenges and the need for secrecy surrounding AAS use, which further hindered open discussions and engagement with healthcare providers. The cohort emphasised the close-knit social networks among AAS users, offering support and shared experiences but also entangled in the criminality associated with AAS use. Moreover, participants acknowledged the difficulties in promoting harm reduction initiatives due to the need for secrecy and the potential social and economic disadvantages. The escalation of AAS criminalisation that has impacted both consumers and healthcare professionals has exacerbated the challenges associated with their interaction, further impeding a relationship already fraught with obstacles. Consequently, users remain entrenched within the illicit market, with few options for harm reduction intervention. The study advocates for a rethinking of AAS policies, considering a potential reclassification aligned with the United Kingdom's Class C framework to destigmatise use and promote harm reduction. This shift would require comprehensive research to assess its impact on public health, user behaviour, and harm reduction outcomes.